2019
DOI: 10.1186/s13063-019-3665-0
|View full text |Cite
|
Sign up to set email alerts
|

Is dangling of the lower leg after a free flap reconstruction necessary? Study protocol for a large multicenter randomized controlled study

Abstract: Background Within the field of plastic surgery, free tissue transfer is common practice for knee and lower leg defects. Usually, after such free flap reconstruction, patients undergo a dangling protocol in the postoperative phase. A dangling protocol is designed to gradually subject the free flap to increased venous pressure resulting from gravitational forces. Worldwide there are multiple variations of dangling protocols. However, there is no evidence available in the literature that supports … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It has also been reported that lower limb free flaps may be at increased risk of venous congestion compared to free flaps applied elsewhere in the body, even when the limb is kept elevated [19] . In light of concerns around venous congestion, the best time from which to permit weight bearing is uncertain, and many centres have introduced "dangling protocols", the aim of which is to introduce gravitational dependency gradually to allow adaptive physiological responses to take place and reduce the risk of flap loss [20] . Systematic reviews have shown that early dangling appears to be safe and may lead to reduced length of stay [1,7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that lower limb free flaps may be at increased risk of venous congestion compared to free flaps applied elsewhere in the body, even when the limb is kept elevated [19] . In light of concerns around venous congestion, the best time from which to permit weight bearing is uncertain, and many centres have introduced "dangling protocols", the aim of which is to introduce gravitational dependency gradually to allow adaptive physiological responses to take place and reduce the risk of flap loss [20] . Systematic reviews have shown that early dangling appears to be safe and may lead to reduced length of stay [1,7] .…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews have shown that early dangling appears to be safe and may lead to reduced length of stay [1,7] . However, a wide variability in practice has been demonstrated in multiple countries, and there is no consensus over the best time to introduce dangling, with even less evidence for weight bearing [1,20,21] . A systematic review of dangling regimes published in 2017 stated that, traditionally, dangling begins on around day 5 but concludes that dangling may be safe from as early as day 3 [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Life 2023, 13, 1158. https://doi.org/10.3390/life13051158 https://www.mdpi.com/journal/life Moreover, flap perfusion and viability are often determined by clinical observation, as well as results obtained by Doppler ultrasonography [6,8]. This is still the gold standard for assessing flap viability [5,9,10].…”
Section: Introductionmentioning
confidence: 99%